Not All Academics Are Alike: First Validation of the Academics' Quality of Life at Work Scale (AQoLW) - Converso, Daniela; Loera, Barbara; Molinengo, Giorgia; Viotti, Sara; Guidetti, Gloria (Frontiers in Psychology, 2018)
Background: Relating to the macro-level changes and the increasing complexity of the academic system, a growing number of studies began to investigate the perceived working context impact on well-being and job satisfaction of academics. A unique duality characterizes this context: academics cannot be longer defined as stress-free, but at the same time they are still satisfied and engaged in their work. There is a need to evaluate the academic environment not only in terms of stressor and strain, but also in terms of which experiences are sources of fulfillment. The study aimed to explore psychometric properties of a new instrument (AQoLW) for assessing context-specific features of the academic work and environment that characterized academics’ quality of life at work. Method: A 24 item scale was deployed to academics (full, associate, and assistant professors) in a public university in the north of Italy. Items were defined to represent the main academic activities in order to measure if respondents perceived each of it as a challenging or a hindrance demand. The scale was administered online to 1012 academics, 443 females (48.7%), mean aged 51.1 years (SD= 8.2). In order to test three theoretical models underling AQoLW, a training sample was randomly extracted (242 participants) and analyzed using confirmatory factor analysis (CFA). A validation sample with the remaining 668 participants was used to test the measurement invariance by role of the best model emerging from the training sample. Results: Model fit demonstrate the goodness of a latent structure composed by five intercorrelated factors (CFI=.91, RMSEA =.08, SRMR = .07). Cronbach of the five subscales was good, ranging from .76-.88. The scale overtakes configural invariance, but not strong invariance by role. Conclusions: The scale is able to intercept the mainly dimensions of the academic work that contribute to the quality of life of academics’ staff, namely: research and public engagement, didactic work and relationships with students, career development and competition, ordinary obligations, and fund raising. AQoLW is the first tool to evaluate the academic work and its environment, identifying which activities are stressful demands and which are engaging, and promote scholars’ satisfaction.